Determinants of morbidity in women undergoing induction of labour. (18th April 2012) - Bonner, SJ; Patel, K; Higgins, L; Mahoney, C; Tower, C
Abstract : Background: Induction of labour (IOL) is conducted in 20% of all UK deliveries. IOL is associated with medicalisation of a natural life event potentially resulting in medical intervention, therefore it is important to ensure that these risks outweigh the benefits of waiting for spontaneous labour. This study aimed to quantify these risks in specific groups. Methods: A retrospective audit in a large tertiary centre was undertaken to establish complication rates in women undergoing IOL. Results: A total of 552 women undergoing IOL were studied, of whom 35 (7%) had undergone previous LSCS. Previous LSCS was associated with a reduced vaginal delivery rate of 60.5% compared with 79% and an increased estimated blood loss of 450mls (interquartile range 300-600mls) compared to 350mls (IQR 200-500mls, p<0.05 Mann-Whitney). Primigravidas overall were less likely to achieve a normal vaginal delivery (NVD) (71% vs 83%, p<0.002, Fishers). IOL for postmaturity was associated with an increased incidence of post partum haemorrhage compared to other indications (42% vs 18%, p<0.01), and these women were more likely to undergo fetal blood sampling (21% vs 11%, p=0.07). The vaginal delivery rate for primigravidas induced for postmaturity was 73%, compared with 91% for multigravidas (p<0.05). Conclusions: Although induction of labour in association with a previous LSCS is associated with increased risks, the majority achieved a vaginal delivery. In particular, this study has suggested that primparous women induced for post maturity and women with a previous LSCS demonstrate the highest complication rates for lower vaginal delivery rates.